Solicitude e respeito ao outro em Paul Ricoeur - Simões, Adelson Cheibel (2013)
Investigate the concepts of Solicitude and Respect in Paul Ricoeur supposes that we enter certainly in his writings on ethics and morals. Therefore, first it is necessary to bear in mind certain considerations such as the distinction made by the philosopher within the field of ethics through the concepts of ethics, referring to the good life and moral which is understood as mandatory. Along the same line we have the concept of care that is developed by Ricoeur from the fact that he did not find in the Aristotelian concept of friendship a sufficiently clear endorsement of otherness. That is the reason why he turns to the concept of solicitude as a possibility of opening and welcoming of another. Secondly we try to justify the thesis of the necessity of submission of ethical intent to proof of standard, since it is in this connection between obligation and formalism that this shock unfolds. The result achieved is that respect for oneself is the correlate of moral self-esteem, constituting itself from corresponding structures. The conclusion we draw is that the respect for oneself, which in the moral aspect corresponds to the respect for oneself of the ethical plane, is just full of meaning when your respect for the rule is expanded with respect to others. Finally, we understand that it is the idea of humanity in my person and the other person that makes us move from the ethical to the moral plane. This change then has resonance in the idea of justice. The problem of justice becomes to establish equitable procedures in order to ensure respect for all the people. At the individual level, justice is the guarantee of liberty, it is respect in interpersonal and in the collective level it translates as the standard which ensures the good coexistence. However, there are conflicts that arise from the application of the rules. And so the purpose of practical wisdom is to settle conflicts so that it is possible to achieve the good life, thinking in a fair way and acting well.